Anti-tumor effect of Yanggan Huayu granule by inducing AKT-mediated apoptosis in hepatocellular carcinoma. (10th January 2022) - Shen, Yang; Yang, Fan; Peng, Haiyan; Zhang, Guangji; Zhu, Fangfang; Xu, Haojun; Shi, Le
Abstract: Ethnopharmacological relevance: Yanggan Huayu granule (YGHY) is a formula of traditional Chinese medicine that has been widely used to treat patients with liver cancer. But its working mechanism is still poorly understood. Aim of the study: To investigate the anti-tumor effect of YGHY and its working mechanisms in hepatocellular carcinoma (HCC). Materials and methods: H22 mouse xenograft model was used to detect the effect of YGHY on hepatocellular carcinoma (HCC). MTT and CCK8 assays were performed to assess the effect of YGHY on HCC cell growth. Transwell assay was performed to detect the invasion and migration activities of HCC cells. Effect of YGHY drug-contained serum on apoptosis was detected by flow cytometry. Western blot was performed to detect the protein expressions. Results: Results showed that YGHY inhibited tumor volume and weight, induced the apoptosis of HepG2 and SMMC-7721 cells and increased the protein expressions of Cleaved-Caspase3 and Cleaved-PARP. Furthermore, YGHY significantly down-regulated the protein expression of p-AKT. SC79, as an activator of AKT signaling, was able to increase the expression of p-AKT, and regulate the protein expressions of Cleaved-Caspase3, Cleaved-PARP, BCL-2 and BAX. YGHY drug-contained serum negated the protein expression change provided by SC79. Conclusions: Taken together, this data indicates that YGHY could inhibit HCC growth by inducing apoptosis, operating through AKT signaling. Graphical abstract: Image 1 Highlights: YGHY inhibited hepatocellular carcinoma both in vivo and in vitro . YGHY induced apoptosis of hepatocellular carcinoma cells. YGHY induced apoptotic signaling mediated by Akt signaling pathway.